ZIRCON IN HIGH‐MG DIORITE OF THE CHELYABINSK MASSIF (SOUTH URALS): MORPHOLOGY, GEOCHEMICAL SIGNATURE, AND PETROGENESIS IMPLICATIONS - T. A. Osipova; G. A. Kallistov; M. V. Zaitseva (Геодинамика и тектонофизика, 2019)
The article is focused on the morphology, trace element composition, U‐Pb and Lu‐Hf systems in zircon in high‐Mg diorite of the Chelyabinsk granitoid massif. Our analytical studies of the U‐Pb and Lu‐Hf isotope systems and the trace element composition were performed using mass spectrometry (MS) with inductively coupled plasma (ICP) and laser ablation (LA) of samples. It is established that the zircon formed at the last stages of crystallization of the basic melt under subsolidus conditions at low (600–700 °C) temperatures, which distinguishes it from the zircon of most other high‐Mg rocks of the intermediate composition. The internal structure of the zircon and the concentration of trace elements are locally altered under the influence of a fluid, which led to a partial disruption of the U‐Pb and Lu‐Hf isotopic systems. For the least altered areas in the zircon crystals, the age of crystallization of the parent high‐Mg melt is 362±2 Ma, which coincides with the age estimated from the geological data. Considering the isotope composition of Hf in the zircon and the trace element concentrations, there are grounds to relate the formation of high‐Mg diorite in the Chelyabinsk granitoid massif with a mixed mantle‐crustal source.